Localized lipoatrophy and inadvertent subcutaneous administration of a COVID-19 vaccine - Ian F. Cook (Taylor & Francis Group, 2022)
A 60-year-old woman presented with a depressed lesion at the site of her first COVID-19 (Astra Zeneca) vaccine injection. The lesion was diagnosed as a case of injection related localized lipoatrophy as markers of autoimmune disease were negative and biopsy differentiated it from localized involutional lipoatrophy. This case of localized lipoatrophy was likely due to inadvertent subcutaneous injection of the COVID-19 vaccine with a 16 mm long needle.